Armillaria ostoyae in managed coniferous forests in Kastamonu in Turkey - Lehtijaervi, Asko Tapio; Dogmus-Lehtijarvi, H. T.; Kaya, A. G. Aday; Unal, S.; Woodward, S. (Wiley, 2017)
Although several Armillaria species have been reported in Turkey, there is little information about their ecology in Turkish forests. In this study, we investigated five forest stands, approximately 5-74ha in size, in Kastamonu province in the Black Sea Region of Turkey for the presence of Armillaria species in stumps and logs. The stands were mixed Abies nordmanniana ssp. bornmulleriana and Pinus sylvestris forests managed using a selective cuttings system; the proportion of fir in the total number of stems and stumps ranged from 36 to 98%. Based on sequence analysis of the internal transcribed spacer and intergenic spacer regions of the rDNA, all rhizomorphs sampled from the stumps and logs were of Armillaria ostoyae. The size of the genets was estimated with random amplified microsatellites analysis of the isolates and ranged from single stumps to approximately 450m(2). One to seven genets were found in each stand. These results indicate that the genets had arisen from spores and vegetative spread was limited on most sites.
Keywords: Abies nordmanniana ssp; bornmulleriana; Genet; intergenic spacer; internal transcribed spacer; Pinus sylvestris; RAMS